Non-spatially lateralized mechanisms in hemispatial neglect. - Husain, M; Rorden, C (2003)
Hemispatial neglect is a common, disabling disorder that results from brain damage, most frequently stroke. Research on patients with neglect has provided important insights into normal brain mechanisms involved in directing attention, representing space and controlling movement. Although much work has focused on the lateralized components of neglect, recent investigations have also revealed deficits that are not spatially lateralized, consistent with new findings from functional imaging, human neuropsychological and monkey electrophysiological studies. Here we propose that understanding the interactions between spatially lateralized and non-lateralized mechanisms provides important insights into the neglect syndrome and the normal functions of brain structures that are commonly damaged in neglect patients, and will contribute to the development of treatments for the condition.